DETERMINATION OF WORK PRODUCTIVITY AND EMPLOYEE PERFORMANCE: ANALYSIS OF WORK DISCIPLINE AND ORGANIZATIONAL CULTURE - Kadir, Irmah (Dinasti International Journal of Digital Business Management, 2022)
Relevant previous research is very important in a research or scientific article. Previous or related research aims to strengthen theories and phenomena about the relationship or influence between predetermined variables. This article reviews the Determination of Work Productivity and Employee Performance: Analysis of Work Discipline and Organizational Culture, A Study of Human Resource Management Literature. The purpose of writing this article is to build a hypothesis of the influence between variables on the research to be carried out. The results of this research library are that: 1) Work Discipline has an effect on Work Productivity; 2) Organizational Culture has an effect on Work Productivity; 3) Work Discipline has an effect on Employee Performance; 4) Organizational Culture has an effect on Employee Performance.